Extending the prenatal Noonan's phenotype by review of ultrasound and autopsy data. (22nd March 2022) - Lamouroux, Audrey; Dauge, Coralie; Wells, Constance; Mousty, Eve; Pinson, Lucile; Cavé, Hélène; Capri, Yline; Faure, Jean‐Michel; Grosjean, Frédéric; Sauvestre, Fanny; Attié‐Bitach, Tania; Pelluard, Fanny; et al.
Abstract: Objectives: The antenatal phenotypic spectrum of Noonan Syndrome (NS) requires better characterization. Methods: This multicenter retrospective observational included 16 fetuses with molecularly confirmed NS admitted for fetopathological examination between 2009 and 2016. Results: Among 12 pathogenic variants (PV) in PTPN11 (80%), 5 (42%) fell between position c.179 and c.182. Ultrasound showed increased nuchal translucency ( n = 13/16, 93%), increased nuchal fold after 15 weeks of gestation ( n = 12/16, 75%), pleural effusions ( n = 11/16, 69%), polyhydramnios ( n = 9/16, 56%), hydrops ( n = 7/16, 44%), cardiovascular ( n = 6/16, 38%) and cerebral ( n = 4/16, 25%) anomalies. Fetopathological examination found dysmorphic features in all cases, cardiovascular anomalies ( n = 12/15, 80%), pulmonary hypoplasia ( n = 10/15, 67%), effusions ( n = 7/15, 47%) and neuropathological anomalies ( n = 5/15, 33%). Hydrops was significantly ( p = 0.02) more frequent in the four fetuses with RIT1, NRAS and RAF1 PV versus the 12 fetuses with PTPN11 PV. Conclusions: Increased nuchal translucency and nuchal fold is common in NS. Noonan Syndrome antenatal phenotype showed high in utero fetal death, hydrops, prenatal pleural effusion and pulmonary hypoplasia, although the inclusion of only deceased fetuses will have selected more severe phenotypes. Non‐specific cardiovascular and neurological abnormalities should be added to NS antenatal phenotype. Next generation sequencing will help detect more genotypes, clarifying the prenatal phenotype and identifying genotype‐phenotype correlations. Key points: What's already known about this topic? Noonan Syndrome (NS) is an autosomal dominant disorder with highly variable antenatal phenotype, which sometimes does not correlate with the severity of the postnatal phenotype, making counseling challenging. The ultrasound phenotype of NS is associated with increased nuchal translucency in first trimester and beyond the second trimester of pregnancy, polyhydramnios, pleural effusion, ascites, edema and cardiac and facial anomalies. These signs are frequent and non‐specific. What does this study add? This case series better characterizes fetuses carrying NS, identifying a wider phenotypic spectrum than originally reported. The antenatal phenotype includes non‐specific cardiovascular, renal and neurological abnormalities. This phenotype seems to be more severe than previously thought, with a high rate of hydrops, prenatal pleural effusion and pulmonary hypoplasia. Different genotypes have specific phenotypes, for example, hydrops was more associated to mutations in non‐PTPN11 targets.